2021
DOI: 10.1021/acs.nanolett.1c00776
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Design of Silver-Bearing Sugar-Based Polymer Nanoparticles for Uroepithelial Cell Binding and Antimicrobial Delivery

Abstract: Platelet-like and cylindrical nanostructures from sugarbased polymers are designed to mimic the aspect ratio of bacteria and achieve uroepithelial cell binding and internalization, thereby improving their potential for local treatment of recurrent urinary tract infections. Polymer nanostructures, derived from amphiphilic block polymers composed of zwitterionic poly(D-glucose carbonate) and semicrystalline poly(L-lactide) segments, were constructed with morphologies that could be tuned to enhance uroepithelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 53 publications
(74 reference statements)
0
30
0
Order By: Relevance
“…In the past decades, nanoscience and nanotechnology have flourished with outstanding progress ( 43 , 44 ). Various antibacterial nanomaterials, including liposomes ( 45 , 46 ), carbon-based nanomaterials ( 47 , 48 ), noble metal NPs ( 49 , 50 ), semiconductor NPs ( 51 ), and polymeric nanomaterials ( 52 ), are being developed as alternative therapeutic options to combat against bacterial infections. These nanomaterials not only could exert a good antibacterial activity by themselves ( 53 ) but also are loaded with antibiotics ( 54 ) or antimicrobial peptides ( 55 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, nanoscience and nanotechnology have flourished with outstanding progress ( 43 , 44 ). Various antibacterial nanomaterials, including liposomes ( 45 , 46 ), carbon-based nanomaterials ( 47 , 48 ), noble metal NPs ( 49 , 50 ), semiconductor NPs ( 51 ), and polymeric nanomaterials ( 52 ), are being developed as alternative therapeutic options to combat against bacterial infections. These nanomaterials not only could exert a good antibacterial activity by themselves ( 53 ) but also are loaded with antibiotics ( 54 ) or antimicrobial peptides ( 55 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent progress in the synthesis of degradable polymer backbones and design of nanoparticles of diverse morphologies have allowed integration into hemostatic composites. [60][61][62][63] However, the types of polymers exploited, shape of nanoscopic features, degradability, and degradation products, might have a great effect on hemostatic efficiency, cyto-and immunotoxicities, and degradation/release kinetics. [64][65][66] More comprehensive studies should be conducted to achieve safe and effective bioabsorbable hemostatic materials, including identification and screening of the metabolites in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Wooley and coworkers [80] fabricated spherical micelles, cylinders and nanoplates derived from the crystallization-driven self-assembly (CDSA) of an amphiphilic block copolymer composed of zwitterionic poly( Very recently, Wooley and coworkers [80] fabricated spherical micelles, cylinders and nanoplates derived from the crystallization-driven self-assembly (CDSA) of an amphiphilic block copolymer composed of zwitterionic poly(ᴅ-glucose carbonate) and semicrystalline poly(ʟ-lactide) segments (PDGC-b-PLLA). As illustrated in Figure 3, fluorescent molecule and cysteine were modified on the polymer in order to afford tracing ability and to chelate with silver ions, respectively.…”
Section: Efficient Delivery Of Antimicrobial Agents By Diverse Polymeric Nanostructures 21 Self-assembled Polymeric Nanoparticlesmentioning
confidence: 99%
“…Battaglia et al [71] reported the intracellular delivery of metronidazole or doxycycline to P. gingivalis-infected oral epithelial cells by polymer vesicles, which were disassembled in early endosomes due to the acidic condition, resulting in the release of loaded cargoes. Very recently, Wooley and coworkers [80] fabricated spherical micelles, cylinders and nanoplates derived from the crystallization-driven self-assembly (CDSA) of an amphiphilic block copolymer composed of zwitterionic poly(ᴅ-glucose carbonate) and semicrystalline poly(ʟ-lactide) segments (PDGC-b-PLLA). As illustrated in Figure 3, fluorescent molecule and cysteine were modified on the polymer in order to afford tracing ability and to chelate with silver ions, respectively.…”
Section: Efficient Delivery Of Antimicrobial Agents By Diverse Polymeric Nanostructures 21 Self-assembled Polymeric Nanoparticlesmentioning
confidence: 99%